THU0370 CLUSTER-RANDOMIZED PRAGMATIC CLINICAL TRIAL EVALUATING THE POTENTIAL BENEFIT OF A TIGHT-CONTROL AND TREAT-TO-TARGET STRATEGY IN AXIAL SPONDYLOARTHRITIS: THE RESULTS OF THE TICOSPA TRIAL. (2nd June 2020) - Moltó, A.; López-Medina, C.; Van den Bosch, F.; Boonen, A.; Webers, C.; Dernis, E.; Van Gaalen, F. A.; Soubrier, M.; Claudepierre, P.; Baillet, A.; Starmans-Kool, M.; Van der Heijde, D.; et al.
Abstract : Background: Current recommendations for axial spondyloarthritis (axSpA) management include tight control and treat-to-target (TC) strategies, but no study has evaluated its potential benefit Objectives: To evaluate the benefit of TC strategies in comparison to usual care (UC) in patients with axSpA. Methods: Study design: Pragmatic, prospective, cluster-randomized controlled (2 arms), one-year trial (NCT03043846 ). Centers : 18 axSpA expert centers randomly allocated (1:1) to the treatment arm: TC vs. UC. Patients : axSpA diagnosis and ASAS criteria, non-optimally treated with NSAIDs, bDMARD-naïve, and ASDAS > 2.1 at inclusion. Study treatment : a) TC arm : the strategy was pre-specified by the scientific committee based on current axSpA recommendations and aiming at a target (ASDAS <2.1); visits every 4w; b) UC arm: treatment decisions were at the rheumatologist's discretion with visits every 12w. Outcomes: the % of patients with a significant (>30%) improvement in the ASAS-HI score over one-year follow-up was the main outcome. Other outcomes (disease activity, quality of life, treatment, …) over follow-up were evaluated (Table 1 ). The number/type of adverse events were collected. Statistical analysis : this was an intention-to-treat analysis. To take into account the cluster-randomization design, for all outcomes, two models were performed: first a two-level mixed model with 2 random effects was used to estimate the % of responders/the change of the outcome over follow-up (i.e. mod1); in a second step, the imbalanced variables observed at baseline were included in the model (i.e.mod2). Cost-effectiveness was assessed by estimating the (baseline- and cluster-adjusted) incremental cost per quality-adjusted life-year (QALY) gained for TC vs. UC. Results: 160 patients were included (80 in TC and 80 in UC). Mean age was 37.9(11.0) years with a disease duration of 3.7(6.2) years, 51.2% were males. A radiographic damage of the SI-joints, a (ever) positive MRI sacroiliitis and HLA-B27+ were seen in 46.9%, 81.9% and 75.0% patients respectively. Mean ASDAS at inclusion was 3.0 (0.7) and mean ASASHI was 8.6 (3.7). 72 patients per group attended the one-year visit. Although 47.3% vs. 36.1% patients in the TC and UC arms achieved a significant improvement in ASASHI at the one-year visit, the difference was not statistically significant, with either model. Across all other outcomes a trend was observed in favor of the TC arm (Table 1 ). The number of bDMARDs was significantly higher in TC arm (56.2% vs. 27.2%). The number of infections was comparable in both groups (15 vs. 16 in the TC and UC, respectively), with only 2 severe infections occurring in the UC arm. From a societal perspective, TC resulted in an additional 0.04 QALY and saved €265 when compared to UC and a 67% probability of being cost-effective at a cost-effectiveness threshold of €20, 000 per QALY. Conclusion: In this setting of SpA expert centers, UC resulted in a good outcome in a substantial number of patients but the TC was not superior for the primary outcome despite a greater number of bDMARDs prescription. Nevertheless, a general trend in favor of the tight control was observed, with a comparable safety profile and was found to be favorable from a societal health economic perspective. Acknowledgments: this trial has been conducted thanks to an unrestricted grant from UCB Disclosure of Interests: Anna Moltó Grant/research support from: Pfizer, UCB, Consultant of: Abbvie, BMS, MSD, Novartis, Pfizer, UCB, Clementina López-Medina: None declared, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Annelies Boonen Grant/research support from: AbbVie, Consultant of: Galapagos, Lilly (all paid to the department), Casper Webers: None declared, Emmanuelle Dernis Speakers bureau: Lilly, Novartis, Floris A. van Gaalen: None declared, Martin SOUBRIER: None declared, Pascal Claudepierre Speakers bureau: Janssen, Novartis, Lilly, Athan Baillet Consultant of: Athan BAILLET has received honorarium fees from Abbvie for his participation as the coordinator of the systematic literature review, Mirian Starmans-Kool: None declared, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV, Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma